2014
DOI: 10.1002/iid3.18
|View full text |Cite
|
Sign up to set email alerts
|

Gamma delta T cells in non‐immune patients during primary schistosomal infection

Abstract: The mevalonate pathway is critical for the survival of Schistosoma. γδ T cells, a small subset of peripheral blood (PB) T cells, recognize low molecular weight phosphorylated antigens in the mevalonate pathway, which drive their expansion to exert protective and immunoregulatory effects. To evaluate their role in schistosomiasis, we measured γδ T cells in the PB of non-immune travelers who contracted Schistosoma hematobium or Schistosoma mansoni in Africa. The maximal level of γδ T-cells following infection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…One strength of our study is that we did not limit our analysis to CD4 T cells, which allowed us to detect a strong γδ T cell response to SWAP antigen. γδ T cells are elevated in the blood of individuals with acute schistosomiasis, however this analysis was not done in an antigen-specific fashion [ 25 ]. Here we provide evidence that γδ T cells respond to SM in an antigen specific manner in that they are activated by SWAP but not by SEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strength of our study is that we did not limit our analysis to CD4 T cells, which allowed us to detect a strong γδ T cell response to SWAP antigen. γδ T cells are elevated in the blood of individuals with acute schistosomiasis, however this analysis was not done in an antigen-specific fashion [ 25 ]. Here we provide evidence that γδ T cells respond to SM in an antigen specific manner in that they are activated by SWAP but not by SEA.…”
Section: Discussionmentioning
confidence: 99%
“…They canonically proliferate and produce IFNγ in response to phosphoantigens produced by pathogens [ 22 , 23 ]. Vγ2Vδ2 T cell populations expand in the peripheral blood of people in response to a variety of infections [ 22 , 24 ] including SM [ 25 ]. While it is clear that γδ T cells respond to infection with helminths, whether they respond to helminth antigen directly or are merely bystander cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…During schistosomiasis, the response to schistosome antigen is primarily mediated by activated CD4 + αβ T cells (33). However, it has also been reported that γδ T cells are recruited to egg-induced granuloma in the murine schistosomiasis (124) and that the levels of γδ T cells are increased in schitosome-infected mice and patients (125,126). However, an earlier study investigating the relative roles of αβ and γδ T cells in the immunopathology of schistosomiasis found that mutant mice lacking γδ T cells display vigorous formation of egg granulomas similar to normal mice, which demonstrates that granuloma formation is not dependent on γδT cells (127).…”
Section: Innate γδ T Cells In Schistosomiasismentioning
confidence: 99%
“…γδΤ cells is one of the subsets of T-lymphocyte with a small number which was found in the recent 30 years, only accounted for 0.5%~5% of the total number of lymphocytes in peripheral blood of adults [1]. Recent studies [1][2][3][4][5] have found that the γδΤ cells in the body played an important role of antiinfection, anti-tumor, immune surveillance, immune regulation and maintenance of immune tolerance. In the past years, the γδΤ cells were separate by flow cytometry or magnetic cell separation technology, not only needing a lot of peripheral blood, but also requiring expensive equipment and complex operations.…”
Section: Introductionmentioning
confidence: 99%